Study of The Main Roots of Digital Economy Within the Research Environment: A Bibliometric Analysis.. - Cristian MARCU; Carmen Nadia CIOCOIU; Nicolae NISTOR (Communications of International Proceedings, 2021)
This research aims to conduct a bibliometric analysis through which to identify the origins of digital economy and where it’s heading, by looking at its main roots and the directions on strategic development. For this will be analyzed the papers within the research environment and the identified related keywords. The research will use as a base the papers extracted from Web of Science Core Collection Database. The selection criteria are being further detailed in Research Methodology section. The results are very compromising, showing the economical reasoning of Digital Economy and where it’s looking now: Internet of Things, Blockchain and others.
Keywords: Digital Economy; Roots; Internet Economy; Bibliometric Analysis